Studies of Al-Ti AHoys by SEM - Yildiz, K.; Atici, Y.; Kelioglu, K.; Yasar, E. (Amer Inst Physics, 2007)
Al-Ti (1, 2 wt. %) alloys were investigated by Scanning Electron Microscopy (SEM). SEM observations and energy-dispersive x-ray analyses (EDX) showed that the phase structure of Al-Ti (1 %) alloy at 165 mu m/s is composed of Al matrix and C, Ni, Fe and Si particles and the Al-Ti (1 %) alloys at 16 and 8 mu m/s have only the Al matrix and C particles. It was also found that the Al-Ti (2 %) form the Al matrix and intermetallic TiAl.
6th International Conference of the Balkan-Physical-Union -- AUG 22-26, 2006 -- Istanbul, TURKEY